Analisis Karya Arsitektur Gedung London Sumatera Melalui Pendekatan Periode Sejarah, Gaya, Arsitektur, dan Karakteristik Bangunan Menggunakan Kode Semiotika - Angga Wiguna; Dara Wisdianti (PT. Arsil Reka Engineering, 2023)
The city of Medan is famous for its many historical buildings scattered throughout the city. The building has a magnificent colonial architectural design. The building's character and unique architectural details make this building different from the others. But it is a shame that these buildings cannot enjoy their beauty at night. Lack of artificial lighting received by the building. This research aims to obtain an overview of people's visual comfort, especially at night. The method used is a qualitative method to understand phenomena experienced by research subjects such as perceptionand by means of descriptions in the form of words and language, in a special natural context. Perceptions regarding the quality of a building's lighting are largely determined by the impression a person has when they see it, either directly orindirectly (using image media or a computer screen). To facilitate the visual description of building lighting at night, modeling was carried out using Enscape software. The results of this research are that the London Sumatra (Lonsum) building has a Dutch colonial architectural style. Some of the characteristics of Dutch colonial architecture found in Lonsum buildings include: verandas that protrude into the street corners, stained glass with geometric motifs on the verandas, marble ceiling and floor tiles, cast iron balustrades on balconies and stairs, art ornaments deco in the interior, such as geometric hanging lamps and beautiful doors. Lonsum is a plantation company founded in 1906 by Harrisons & Crosfield Plc, a general trading and plantation management services company from London, England.